Fatigue performance of overhead conductors tested under the same value of H/w parameter. (2018) - Kalombo, R.B.; Miranda, T.B.; Rocha, P.H.C.; Ferreira, J.L.A.; da Silva, C.R.M.; Araújo, J.A.
Abstract: The objective of this work is to conduct an experimental campaign to evaluate the effects of the catenary parameter ( H/w ) on the fatigue life of overhead conductors, being H the horizontal tensile load of the power line and w the weight per unit length of the conductor. A battery of twenty seven (27) fatigue tests was carried out on three types of conductors, an AAAC 900 MCM, an AAC Orchid and an ACSR Tern. For this study, all tests were conducted using the value of H/w = 2144 m. Fatigue damage, one of the major problems affecting power line conductors around the world, is caused by Aeolian vibration, characterised by high frequency and low amplitude movements. Based on field observations, the H/w parameter has recently been proposed as a fatigue design criterion for different families of cables. However, there is little experimental data available in the literature to assess the impacts of this hypothesis. Comparison between the generated S-N curves proved that an ACSR Tern conductor could sustain a significantly higher number of cycles before fatigue failure than the AAAC 900 MCM for this level of H/w . Meanwhile, the AAC Orchid presents a fatigue life situated between the AAAC 900 MCM and the ACSR Tern conductors. Failure analysis of the broken samples revealed not only that cracks initiated in the fretted areas of the aluminium wires but also that their morphology presented clear evidence of fatigue failure, such as observable beach marks and secondary cracks. Additionally, a failure map has been raised to determine the precise layer and the position from the clamp mouth where the wires broke. Furthermore, the provided information could be helpful for planning the maintenance of power lines.